Comparison of power cycling reliability of flexible PCB interconnect smaller/thinner and larger/thicker power devices with topside Sn-3.5Ag solder joints - Li, Jianfeng; Dai, Jingru; Johnson, Christopher Mark (Elsevier, 2018)
The power cycling reliability of flexible printed circuit board (PCB) interconnect smaller/thinner (ST) 9.5 mm × 5.5 mm × 0.07 mm and larger/thicker (LT) 13.5 mm × 13.5 mm × 0.5 mm single Si diode samples have been studied. With the assumption of creep strain accumulation-induced fatigue cracking as the failure mechanism of the Sn-3.5Ag solder joints, finite element (FE) simulations predicted a higher power cycling reliability of soldering the flexible PCB on a ST Si diode than on a LT Si diode under similar power cycling conditions. Then the power cycling test results of 10 samples for each type are reported and discussed. The samples were constructed with commercially available ST Si diodes with 3.2/0.5/0.3 μm thick AlSiCu/NiP/Pd topside metallization and LT Si diodes with 5/0.1/1/1 μm thick Al/Ti/Ni/Ag topside metallization. In contradiction with the FE prediction, most ST Si diode samples were less reliable than those LT Si diode samples. This can be attributed to the fact that the failure of the ST diode samples was associated with the weak bonding and hence the shear-induced local delamination of the topside solder joints from the AlSiCu metallization, while the failure of the LT diode samples was mainly caused by the creep strain accumulation-induced fatigue cracking within the solder joints. Such results can be used to not only provide better understanding of the different failure mechanisms, but also demonstrate the importance of employing an appropriate topside metallization on the power devices.